Gunshot injuries to the lower extremities: Issues, controversies and algorithm of management. Issue 7 (July 2020) - Maqungo, Sithombo; Kauta, Ntambue; Held, Michael; Mazibuko, Tamsanqa; Keel, Marius JB; Laubscher, Maritz; Ahmad, Sufian S.
Abstract: Civilian gunshot violence is common and concentrated in specific geographic regions of the world, consuming a significant proportion of trauma practice in those particular regions. Unfortunately, the state of clinical evidence is scarce, and it is fair to emphasize that the field is scientifically under-represented. In the current review, the authors point out key aspects and principles requiring attention when treating low energy gunshot wounds to the lower extremity. These treatment principles include the following management concepts: 1) Conservative management of soft tissue injuries if the projectile causes no discomfort. 2) Conservative management of non-complete fractures of the tibia or femoral shaft. 3) Prophylactic fixation of non-complete peri-trochanteric fractures. 4) Fixation of allcomplete fractures. 5) Removal of all intra-articular projectiles. 6) Treating as septic arthritis if the missile passes through large bowel (not small bowel) prior to penetrating a joint capsule. The proposed concepts are based on available evidence from the literature and expert opinion. The authors also highlight challenges with conducting clinical studies in the field, given the high rate of 'loss to follow-up' and compliance issues in this particular group of patients.